Sistem Keamanan Kendaraan Berbasis Mikrokontroler Arduino Menggunakan Sensor NFC - Rosidin (Jurnal Komputer dan Informatika, 2024)
Based on information from Polda Metro Jaya, vehicle theft cases continue to increase. This is possible due to the lack of security features on vehicles. Security features on vehicles can be added by utilizing Internet of Things technology. One of the uses of Internet of Things technology as a security is by using an Arduino microcontroller. The Arduino microcontroller in this study will be used together with an NFC sensor and a Relay sensor. With the combination of the microcontroller and the sensor, even though the key is on, the motorbike still cannot be turned on if the NFC sensor has not detected the RFID Tag that matches its program.